BOARD CHARACTERISTICS, GOOD CORPORATE GOVERNANCE AND MAQȂSHID PERFORMANCE IN ISLAMIC BANKING - Muhammad Wahyudi Pranata; Sugiyarti Fatma Laela (Journal of Islamic Monetary Economics and Finance, 2020)
This research aims to examine the effect of the characteristics of the board on the Maqâshid Shariah Index (MSI) performance of Indonesian Islamic banks, using panel data regression. Independent variables, namely the characteristics of the board of commissioners, board of directors, and shariah supervisory board are related to board internal ownership, board expertise, board independence, cross-membership board, and board tenure with size and growth as controlling variables, while the dependent variable is Maqâshid Shariah Performance in Islamic Banks. The samples of this study include 12 Islamic banks in Indonesia, which regularly publish their annual reports and management for the period 2009-2017. The results from both models, with and without control variables, show that board ownership (commissioner and director), board cross-membership (commissioner and Shariah supervisor) and Shariah supervisor expertise do not have impact to MSI. Moreover, the results from model without control variables show that commissioner expertise has positive impact to MSI, while board tenure (commissioner and director) and commissioner independence do have negative impact to MSI. These results provide recommendations for the Islamic banking industry, so that it can be applied optimally to achieve the main objectives of the maqâshid Shari’ah.